(untitled) (International Journal of Food and Nutritional Sciences, 2022)
It is not always possible for an author to convey their thoughts clearly using words. So, they use symbols as a tool to convey deeper meanings. Symbolism gives a writer freedom to add double levels of meaning to his work: literal one that is self-evident and a symbolic one whose meaning is far more profound than the literal one. Symbolism gives universality to the characters and the themes of a piece of literature. Symbolism is the use of symbols to signify ideas and qualities by giving them symbolic meanings that are different from their literal sense. Symbolism is the art of using an object or word to represent an abstract idea. Dan Brown is essentially a symbolist whose works are filled with symbols. Dan Brown wants to reveal some of the secret symbols hidden in Leonardo‟s works. To him, extensive use of symbols is a necessity to convey his ideas.